VEGF and MVD expression in sinus augmentation with autologous bone and several graft materials - Boeck-Neto, R. J. [UNESP]; Artese, L.; Piattelli, A.; Shibli, J. A.; Perrotti, V.; Piccirilli, M.; Marcantonio, E. [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
The aim of this study was to assess vascular endothelial growth factor (VEGF) expression and microvessel density (MVD) in maxillary sinus augmentation with autogenous bone and different graft materials for evaluating their angiogenic potential.Biopsies were harvested 10 months after sinus augmentation with a combination of autogenous bone and different graft materials: hydroxyapatite (HA, n = 6 patients), demineralized freeze-dried bone allograft (DFDBA, n = 5 patients), calcium phosphate (CP, n = 5 patients), Ricinus communis polymer (n = 5 patients) and control group - autogenous bone only (n = 13 patients).In all the samples, higher intensities of VEGF expression were prevalent in the newly formed bone, while lower intensities of VEGF expression were predominant in the areas of mature bone. The highest intensity of VEGF expression in the newly formed bone was expressed by HA (P < 0.001) and CP in relation to control (P < 0.01) groups. The lowest intensities of VEGF expression in newly formed bone were shown by DFDBA and polymer groups (P < 0.05). When comparing the different grafting materials, higher MVD were found in the newly formed bone around control, HA and CP (P < 0.001).Various graft materials could be successfully used for sinus floor augmentation; however, the interactions between bone formation and angiogenesis remain to be fully characterized.
Keywords: graft materials; guided bone regeneration; maxillary sinus augmentation; microvessel density; vascular endothelial growth factor